STRATEGI DAN PELUANG PEMBELAJARAN PAI BERBASIS MULTIKULTURAL - Nur asih istiqomah; Migfar Rivadah; Mohamad Nizar Potabuga; Arif Rahman (IAIN Purwokerto, 2020)
This research aims to describe the strategies and opportunities for Islamic Education teachers in implementing multicultural learning in schools. The research method used is a descriptive method, how the application of multicultural education to Islamic Education learning is analyzed through supporting literature. This approach uses a qualitative approach with descriptive data, namely data collected using words. In discussing the problem in this article, the writer uses this type of library research. Library research is carried out by collecting data and information from library sources such as books, journals, documents and other library sources. The results of this study are : First, the reason why multicultural education must be taught in Islamic education learning is that there are differences in the backgrounds of students which include different ethnicities, races, and religions; Second, several schools in Indonesia only have one religious lesson, namely Islamic religious lessons so that non-Muslim students are enthusiastic about taking Islamic religious lessons, especially social relations (muamalah) material. With the presence of non-Muslim student participants, teachers can make this moment a form of multicultural education; Third, the strategy of Islamic Education teachers in implementing Teaching and Learning Activities (KBM) in the classroom with the right method, namely lectures then discussions and questions and answers so that all students have the opportunity to provide arguments or opinions regarding Islamic religious material that has been conveyed by the teacher. Fourth, the opportunity for teachers to develop PAI material to have multicultural nuances so that it has an impact on students' beliefs that humans will not be able to live without social contracts with other community groups so that students are expected not to focus on their respective religious groups.